Erythrocyte Long Chain Omega 3 Fatty Acids Are Associated with Higher Lean Mass in Postmenopausal Women Newly Diagnosed with Breast Cancer (P05-024-19). (13th June 2019) - Belury, Martha; Cole, Rachel; Andridge, Rebecca; Xie, Qing; Keiter, Ashleigh; KIecolt-Glaser, Janice
Abstract: Objectives: Cancer contributes to adverse changes in body composition that may increase risk of cardiometabolic diseases. Skeletal muscle is a main driver of cardiometabolic health. We hypothesize that higher intake of long chain omega-3 polyunsaturated fatty acids (LCn3PUFAs) is associated with muscle health. This study evaluates whether LCn3PUFA exposure assessed in diet and in blood is associated with markers of muscle health in women with breast cancer. Methods: This is a cross-sectional analysis evaluating LCn3PUFA exposure and markers of muscle health in women ( N = 150) prior to treatment for breast cancer. Exposure to LCn3PUFAs was assessed by a diet history questionnaire (DHQ), a question specifically about supplement usage and biomarker of LCn3PUFAs in red blood cells (RBC). Body composition were measured at the same visit using dual x-ray absorptiometry. Linear regression models were used to test for associations. Results: 13% ( N = 19) of women reported using fish oil supplements (e.g., Supplement Users) and had significantly higher levels of RBC LCn3PUFAs than Supplement Non-users. In Supplement Non-users, there was a positive association between reported dietary exposure by DHQ and RBC LCn3PUFA levels. The n3 index (e.g., sum of RBC EPA + DHA) and DHA (22:6n3) were positively associated with appendicular lean mass/BMI. There were no significant correlations between RBC LCn3PUFAs with grip strength and or other measurements of body composition. Conclusions: As a biomarker of intake, RBC LCn3PUFAs are positively associated with appendicular lean mass, a measure of skeletal muscle mass. A future study should prospectively evaluate whether higher LCn3PUFA exposure (as measured in blood) is associated with maintaining better muscle health during and following cancer treatment. Funding Sources: Funding was provided by the National Cattleman's Beef Association, NIH (JKG) CA186720, Ohio Agriculture Research and Development Center and the Carol S. Kennedy Professorship.